The Prophylactic Role of Lipoic Acid as an Antioxidant on the Oxidative Status and Histological Structure of Ovaries and Oviducts in Mesterolone Treated Rabbits - Saud, Mustafa A. (International Journal of Psychosocial Rehabilitation, 2020)
Background: We investigated the effect of α-lipoic acid (ALA) on the administration of anabolic androgenic steroids (AAS) into the rabbit ovary. Changes in the levels of malondialdehyde (MDA) in tissues, the final product of lipid peroxidation, carbonyl protein content (PCC) are usually used as a marker of protein oxidation, regulation of Nrf2 as a sensor of oxidative stress, and histopathological data of the ovaries and oviduct were scored and compared among groups. Materials and methods: Twenty female rabbits were divided into four groups(n = 5 in each group). The control was performed in group (CTRL); in group (Mest) AAS (Mesterolone) received an oral dose of 0.06 mg / kg. Group (ALA) was treated with 50 mg/kg of the alpha lipoic acid and The combined group (Mest + ALA) received both Mesterolone and ALA orally every day for 60 days. After the end of experiment, animals were killed, and samples of ovaries and oviduct tissue from both testes were taken for RNA isolation, biochemical analysis and histological studies. Results: The rates of ovarian tissue damage in different groups were significantly different, and it was found that the MDA levels in the ovarian tissues in the (Mest) group were significantly higher than in the (CTRL) and (ALA) groups (P